Bibliometric Analysis of Human Resource Management Research in the Field of Health Services during the COVID-19 Pandemic: 2019-2023 Study - Jati, Hendra (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2023)
Purpose – This paper presents and discusses the mapping of the research landscape in the field of Human Resource Management (HRM) in the field of health services, especially during 2019-2023. This research was conducted through bibliometric analysis of major journals and publications. Through this approach, we analyze the patterns, trends, and characteristics of publications related to HRM in the health care sector that have been published. Design/methodology/approach – Bibliographical data was obtained from Scopus database sources, including leading journals and trusted publications in the field of HRM. We analyze the country where the research was conducted, local and global citation analysis. In addition, we also analyze citation patterns, map collaboration networks between authors, and identify the most dominant research themes in the HRM field over the last 5 years using VOSviewer software. Originality - Findings and Discussion – The results of research by mapping using the keywords "healthcare", "health service", "human resource", and "human resource development" during 2019-2023 obtained 8,680 articles which were then filtered into 236 articles and 138 articles were eligible to use. The country with the highest contribution was India with a percentage of 18.44%, then England with a percentage of 15.53%, Australia with 14.56%, and the United States with 12.62%, the rest were other countries. Based on trend analysis using keywords, in the period before 2020 the research keywords that appeared a lot were behavioral research, environmental management, environmental performance, customer satisfaction, quality control, competition, etc. During the period of the outbreak of COVID-19, the research keywords that appeared a lot were keywords related to members of health service agencies, especially in the service and performance of health workers. In the period after COVID-19 had subsided, the focus was on efforts to revive the health care sector from the COVID-19 pandemic by increasing the productivity of health workers through strategic human resource management and improving internal communications. Conclusion – Based on the trend, it is advisable to research topics that are rarely discussed such as green human resource management, IoT, digitalization and the use of quantitative analysis such as Structural Equation Modeling.